The Fight for Life: The Convergence of the Print Press in the Digital Media Industry - Hutomo, Mulyono Sri; Ritonga, Rajab (Persatuan Wartawan Indonesia, 2021)
The mass media industry particularly print media in Indonesia comes under heavy pressure to survive in the era of digital disruption. High printing costs, coupled with high distribution costs and employee salaries have caused difficulties for print media companies to maintain their businesses. Some print media companies have opted to shut down their businesses, while others have to survive by making various efficient efforts and diversifying their businesses. The convergence of print media into digital media has offered an alternative to maintain print media as the management of Telaah Strategis magazine has done. This research aims to see the efforts made by the management of Telaah Strategis magazine to survive in the media industry in Indonesia. The results of this research show that Telaah Strategis magazine uses a variety of media convergence models to be able to maintain its task of disseminating information by transforming it into a news portal and digital magazine and appearing in the social media platform. In addition, it also markets its digital magazine at online product sale exchange.